Transcriptome analysis and reverse engineering verification of SNZ3Val125Ile and Pho3Asn134Asp revealed the mechanism of adaptive laboratory evolution to increase the yield of tyrosol in Saccharomyces cerevisiae strain S26-AE2 - Na Song; Huili Xia; Xiaoxue Yang; Siyao Liu; Linglong Xu; Kun Zhuang; Lan Yao; Shihui Yang; Xiong Chen; Jun Dai (Biotechnology for Biofuels and Bioproducts)
Abstract Background Tyrosol is an important drug precursor, and Saccharomyces cerevisiae is one of the main microorganisms that produces tyrosol. Although excessive metabolic modification increases the production of tyrosol, it also causes a decrease in the growth rate of yeast. Therefore, this study attempted to restore the growth of S. cerevisiae through adaptive evolution and further improve tyrosol production. Results After the adaptive laboratory evolution of S. cerevisiae S26, three evolutionary strains were obtained. The biomass of strain S26-AE2 reached 17.82 g DCW/L in the presence of 100 g/L glucose, which was 15.33% higher than that of S26, and its tyrosol production reached 817.83 mg/L. The transcriptome analysis revealed that, upon exposure to 100 g/L glucose, the S26-AE2 strain may reduce the transcriptional regulation of glucose repression through decreased HXK2 expression. The expression of genes related to pyruvate synthesis was increased in strain S26-AE2. Meanwhile, the expression levels of most tricarboxylic acid cycle-related genes in S26-AE2 were increased when cultured with 20 g/L glucose. Furthermore, the amount of tyrosol produced by strain S26 with the SNZ3Val125Ile mutation increased by 17.01% compared with that of the control strain S26 following exposure to 100 g/L glucose. Conclusions In this study, a strain, S26-AE2, with good growth and tyrosol production performance was obtained by adaptive evolution. The transcriptome analysis revealed that the differences in the expression of genes involved in metabolic pathways in adaptive evolutionary strains may be related to yeast growth and tyrosol production. Further reverse engineering verified that the mutation of SNZ3 promoted tyrosol synthesis in S. cerevisiae in glucose-rich medium. This study provides a theoretical basis for the metabolic engineering of S. cerevisiae to synthesise tyrosol and its derivatives. Graphical Abstract